Efektifitass Layanan Konseling Kelompok dalam Menigkatkan Self Adjustment Santri Kelas VII Pondok Pesantren An-Nur Tangkit Muaro Jambi - Barokatun Nikmah; Nurus Sa'adah (Institut Agama Islam Negeri Curup, 2022)
This research is based on the phenomenon that occurred at Pondok Pesantren An-Nur Tangkit, it appears that new students have difficulty in adapting. Some students were caught running away from the Islamic boarding school without permission from the caregivers because they admitted that they did not feel comfortable living in the Islamic boarding school environment which bound the students with many rules. The purpose of this experimental study was to see the extent to which group counseling services were effective in increasing the Self Adjustment of class VII students at the An-Nur Tangkit Islamic Boarding School, Muaro Jambi. The research method used in this study is a research experiment with a quantitative approach. The research design used was Quasi Experimental Design, while the research design used one group pretest post-test. Through this design, the study was conducted in only one group by taking two measurements, namely O1 (pre-test) to measure the level of Self Adjustment of students before being given group counseling services. The results showed that group counseling services could improve the Self Adjustment of class VII students at Pondok Pesantren An-Nur Tangkit Muaro Jambi.